Upaya Mengatasi Cekaman Kekeringan pada Tanaman Nilam (Pogostemon cablin Benth.) dengan Memanfaatkan Kompos Kiambang - Gusta, Adryade Reshi; Kusumastuti, Any (Politeknik Negeri Lampung, 2017)
Productivity and quality of patchouli is influenced by environmental factors especially drought stress. This study aim is to determine application of giant salvinia compost for resolving drought stress on patchouli. This study used a randomized block design and experiment with three replication arranged in factorial 3x4. The first factor is percentage of drought stress 0% (L0), 40% (L1), and 80% (L2). The second factor is application of giant salvinia compost, topsoil 100% (G0), topsoil and giant salvinia compost 1:1 (G1), topsoil and giant salvinia compost 2:1 (G2), and topsoil and giant salvinia compost 3:1 (G3). The result showed that giant salvinia affected increasing on plant height, number of branch, the ratio of root-shoot dry weight, and patchouli oil content. Keywords: growth medium, patchouli oil content, soil moisture